Truly madly guilty - Moriarty, Liane (New York : Flatiron Books, 2016)
"The new novel from Liane Moriarty, the #1 New York Times bestselling author of The Husband's Secret, Big Little Lies, and What Alice Forgot, about how sometimes we don't appreciate how extraordinary our ordinary lives are until it's too late. "What a wonderful writer--smart, wise, funny." --Anne Lamott Six responsible adults. Three cute kids. One small dog. It's just a normal weekend. What could possibly go wrong? In Truly Madly Guilty, Liane Moriarty turns her unique, razor-sharp eye towards three seemingly happy families. Sam and Clementine have a wonderful, albeit, busy life: they have two little girls, Sam has just started a new dream job and Clementine, a cellist, is busy preparing for the audition of a lifetime. If there's anything they can count on, it's each other. Clementine and Erika are each other's oldest friends. A single look between them can convey an entire conversation. But theirs is a complicated relationship, so when Erika mentions a last minute invitation to a barbecue with her neighbors, Tiffany and Vid, Clementine and Sam don't hesitate. Having Tiffany and Vid's larger than life personalities there will be a welcome respite. Two months later, it won't stop raining, and Clementine and Sam can't stop asking themselves the question: What if we hadn't gone? In Truly Madly Guilty, Liane Moriarty takes on the foundations our lives: marriage, sex, parenthood, and friendship. She shows how guilt can expose the fault lines in the most seemingly strong relationships, how what we don't say can be more powerful than what we do, and how sometimes it is the most innocent of moments that can do the greatest harm"--
A busy couple formerly on the brink of realizing their dreams reflects on a fortuitous gathering with their best friends and another couple, in a tale that explores the role of guilt in relationships and the power of everyday moments in family life.
Keywords: Couples -- Fiction; Friendship -- Fiction; FICTION / Family Life; FICTION / Contemporary Women; FICTION / Psychological; Man-woman relationship -- Fiction; Family life -- Fiction; Domestic fiction